Intergrating the English Language Teaching and Learning Process with Soft Skills - Azwar Abbas (International Conference on Education and Language (ICEL), 2013)
In welcoming the 21st century, education in Indonesia faces big challenges to prepare competent human resources in order that they are competitive in the global market. Changes in educational policies have been made by the government to improve the quality of education in Indonesia. The success of education is not only the matter of getting much knowledge by students. Students are also demanded to have soft skills in order to be able to compete with others and to be independent or autonomous. Students must also know the nature of learning and use their knowledge and skills to solve problems in their life. One of the important ways to make students capable of solving problems in their life is by integrating and developing soft skills in the teaching and learning process, including English language teaching and learning. This paper aims at (1) describing the nature of soft skills in the context of English language teaching and learning and (2) describing the process of integrating the soft skills in the lesson plan, the instructional materials, the instructional activities, and the assessment of the students’ achievement. Therefore, this paper is expected to give teachers of English practical procedures of integrating soft skills in their English language teaching and learning so that Indonesian students are really ready to face challenges in the global market.